INDICADORES SOCIOAMBIENTAIS PARA AVALIAÇÃO DE IMPACTO: SISTEMA ESPECIALISTA AMBIENTAL COMO INSTRUMENTO GESTÃO AMBIENTAL - Batista, Gisele Victor (2012)
This article aims to present the relation between the selected socio environmental indicators used to make the expert system environment (SEA) as tool for automate the process of viability consultation for implementation of new constructions, which tends to increase the agility of the public administration within the control of use and occupation of municipal land. The development of this tool is justified since the urban growth in most Brazilian cities has promoted sociospatial segregation, marginalization of the poor and degradation of natural environments. To elaborate the conceptual model of the SEA, the present study has selected socio environmental indicators and, also, has used parameters of environmental law and land use. For each indicator was determined a value that is measured by a checklist procedure and for the analysis of the legislation and crossed with the city’s basemap. Thus, it was made a connection between the characterizations of the environment versus the type of work in viability, resulting in a graph which allowed measuring the significant environmental impact. The implementation of the environmental modeling system encounters the instrumentalization of the municipal administration, which will feature modern land management tool.